URGENSI STUDI TENTANG PROCUREMENT CONTRACT - Yohanes Sogar Simamora (Perspektif, 2006)
Contractualization is kind of goverment activity in acquiring goods, services and infrastructure as well. Procurement contract has several important function especially in enhancing economic development in a state. In Indonesia, this kind of contract also has function in empowering micro economic scale. Since the aim of procurement study is to provide equal protection between public fund interest in one hand and privat sector in the other hand, general principle of contract law must be taken into consideration together with transparency as the most important principle in government contract.